2008
DOI: 10.5089/9781451869804.001
|View full text |Cite
|
Sign up to set email alerts
|

Investment and Growth Dynamics: An Empirical Assessment Applied to Benin

Abstract: This Working Paper should not be reported as representing the views of the IMF. The views expressed in this Working Paper are those of the author and do not necessarily represent those of the IMF or IMF policy. Working Papers describe research in progress by the author and are published to elicit comments and to further debate. We investigate the nexus of public and private investment and assess the impact of both types of investment on growth. Using annual data for 1965-2005, we employ a coherent set of struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
3
0
2
Order By: Relevance
“…In particular, Munnell (1990) reported that for every 10% increase in public investment in economic infrastructure, GDP increased by 1.4% for the USA economy. Similar evidence of the crowding in effect of infrastructure public investment on private investment was supported in studies such as Cullison (1993), Ramirez (1996), Pereira (2001), Erden & Holcombe (2005), Samake (2008) and Sahoo et al (2010), Xiaoming Xu & Yanyang Yan (2014), among others. Empirical evidence of the crowding out effect of public investment on private investment growth is extensive (Evans & Karras, 1994;Nazmi & Ramirez, 1997;Odedokun, 1997;Ghali, 1998;Zou, 2003;Eduardo & Christian, 2011;Xiaoming Xu & Yanyang Yan, 2014).…”
Section: Literature Reviewsupporting
confidence: 59%
“…In particular, Munnell (1990) reported that for every 10% increase in public investment in economic infrastructure, GDP increased by 1.4% for the USA economy. Similar evidence of the crowding in effect of infrastructure public investment on private investment was supported in studies such as Cullison (1993), Ramirez (1996), Pereira (2001), Erden & Holcombe (2005), Samake (2008) and Sahoo et al (2010), Xiaoming Xu & Yanyang Yan (2014), among others. Empirical evidence of the crowding out effect of public investment on private investment growth is extensive (Evans & Karras, 1994;Nazmi & Ramirez, 1997;Odedokun, 1997;Ghali, 1998;Zou, 2003;Eduardo & Christian, 2011;Xiaoming Xu & Yanyang Yan, 2014).…”
Section: Literature Reviewsupporting
confidence: 59%
“…The extant growth literature related to this research topic deals with the relation between investment and economic growth. Empirical evidence has shown that investment has a strong and positive impact on economic growth (Mohsin and Reinhart, 1990; De Long and Summers, 1991; Summers and Heston, 1991; Blomström et al ., 1996; McGrattan, 1998; Bernanke and Gürkaynak, 2001; Farmer and Lahiri, 2006; Samake, 2008). Coupled with a documented close relation between investment and savings across countries, this further implies an association between saving and economic growth (Farmer and Lahiri, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In other words, public and private investments are complementary. Samake (2008) found that public investment crowds in private investment, and that both types of investment have a significant impact on growth in Benin. Similar evidence has also been provided for Cameroon (Ghura, 1997).…”
Section: Empirical Reviewmentioning
confidence: 99%